Performance correlation between YBa2Cu3O7−δ coils and short samples for coil technology development. (15th April 2016) - Wang, X; Dietderich, D R; Godeke, A; Gourlay, S A; Marchevsky, M; Prestemon, S O; Sabbi, G L
Abstract: A robust fabrication technology is critical to achieve the high performance in YBa2 Cu3 O 7 − δ (YBCO) coils as the critical current of the brittle YBCO layer is subject to the strain-induced degradation during coil fabrication. The expected current-carrying capability of the magnet and its temperature dependence are two key inputs to the coil technology development. However, the expected magnet performance is not straightforward to determine because the short-sample critical current depends on both the amplitude and orientation of the applied magnetic field with respect to the broad surface of the tape-form conductor. In this paper, we present an approach to calculate the self-field performance limit for YBCO racetrack coils at 77 and 4.2 K. Critical current of short YBCO samples was measured as a function of the applied field perpendicular to the conductor surface from 0 to 15 T. This field direction limited the conductor critical current. Two double-layer racetrack coils, one with three turns and the other with 10 turns, were wound and tested at 77 and 4.2 K. The test coils reached at least 80% of the expected critical current. The ratio between the coil critical currents at 77 and 4.2 K agreed well with the calculation. We conclude that the presented approach can determine the performance limit in YBCO racetrack coils based on the short-sample critical current and provide a useful guideline for assessing the coil performance and fabrication technology. The correlation of the coil critical current between 77 K and 4.2 K was also observed, allowing the 77 K test to be a cost-effective tool for the development of coil technology.